In the shadows of cancer. Leisure and subjective wellbeing of breast and ovarian cancer patients in Honduras, Nicaragua and Portugal - Chamorro, E.; Barroso, M. (Women, 2021)
In contemporary societies, a significant proportion of women will be affected by breast or ovarian cancer over the course of their lives. Dealing with illness is known to impact profoundly on the general quality of life of women, but this assessment is usually made in clinical terms, and less attention is given to the social determinants of quality of life for cancer patients, and to the implications of cancer for their subjective wellbeing. In this article, we specifically discuss the impact of being engaged in a leisure activity for the subjective wellbeing of women experiencing breast or ovarian cancer. Based on an exploratory comparative study among Honduras, Nicaragua and Portugal, we analyze the influence of leisure engagement, country of residence, treatment and social support for the subjective wellbeing of women dealing with cancer, proposing a discussion on the intersections of wellbeing, leisure and illness. The research was supported by a survey applied to 128 women diagnosed with breast and ovarian cancer. Significant relationships were found amongst subjective wellbeing, leisure engagement, country and support from patients’ associations. Results highlight the need to consider the effects of leisure among cancer patients, and the importance of institutionalized support to improve their quality of life.